What Is the Minimum Clinically Important Change in Negative Symptoms of Schizophrenia? PANSS Based Post-hoc Analyses of a Phase III Clinical Trial - Czobor, Pál; Sebe, Barbara; Acsai, Károly; Barabássy, Ágota; Laszlovszky, István; Németh, György; Furukawa, Toshi A.; Leucht, Stefan (Frontiers in Psychiatry, 2022)
Introduction Minimum clinically important difference (MCID) is a measure that defines the minimum amount of change in an objective score of a clinical test that must be reached for that change to be clinically noticeable. We aimed to find the MCID for patients with predominantly negative symptoms of schizophrenia at its earliest occurrence. Methods Data of a 26-week long, double-blind study with 454 patients (Positive and Negative Symptom Scale Negative Factor Score (PANSS-FSNS) ≥24, Positive and Negative Symptom Scale Positive Factor Score (PANSS-FSPS) ≤19) treated with cariprazine 4.5 mg/d or risperidone 4 mg/d were analysed. The Clinical Global Impression – Improvement scale was used to quantify minimum improvement (CGI-I=3) and no clinical change (CGI-I=4) on the PANSS-FSNS, and the MCID was estimated with various methods: as the mean PANSS-FSNS changes corresponding to the first instance of minimal improvement across all visits (MCID1); as the difference between the PANSS-FSNS change associated with the first instance and the PANSS-FSNS changes associated with the last recorded clinically unchanged status across all visits (MCID2); with the effect size approach (MCID3); as the Youden Index based cut-off value between no clinical change and minimal improvement (MCID4); as the relative likelihood of minimal improvement (MCID5). Results The MCID1 and MCID2 resulted in, respectively, a 3.8-point (18.5%) and a 1.5-point (7.3%) decrease from baseline severity on the PANSS-FSNS. Greater values were required for the MCID at later evaluation times. The cut-off between minimum improvement and no clinical change defined by the Youden Index was a -3-point (15%) change in the PANSS-FSNS. The effect size approach indicated the 1.5-point difference between minimally improved and unchanged patients to be a medium effect (ES=0.6). Conclusion Applying different methods lead to different results, ranging between 7.3% and 18.5% improvement from baseline for the MCID at its earliest occurrence in patients with predominant negative symptoms of schizophrenia.